Novel sustained release and swellable gastroretentive dosage form for ciprofl oxacin hydrochloride - Gaikwad, Vinay Dhananjay; Yadav, Vishal Dadasaheb; Gaikwad, Manish Dhananjay (International Journal of Pharmaceutical Investigation)
Introduction: The present study aims at developing a gastroretentive swellable and fl oating matrix tablet formulation of ciprofl oxacin hydrochloride (HCl) for the effective treatment of infections caused by susceptible organisms. Ciprofl oxacin HCl is a fl uoroquinoline antibiotic drug. Ciprofl oxacin HCl is more stable in acidic medium and it has a narrow absorption window which is sited at the stomach and proximal portions of the small intestine, so it covers the required criteria for selection of drug for gastroretentive dosage form. Materials and Methods: Ciprofl oxacin HCl gastroretentive tablets were formulated by using direct compression method and different grades of hydroxypropyl methylcellulose as suspending and stabilizing agent (polymer), sodium starch glycolate (SSG), crospovidone as disintegrates, sodium bicarbonate as alkalizing agent and magnesium stearate as lubricant. Results: The tablets were evaluated for post compression parameters. All the parameters were within the pharmacopoeial limits. Conclusion: The in vitro dissolution studies showed that the drug release was fast in formulations F2, F4 and F6 containing SSG as super disintegrant when compared with all other formulations. In SEM study of F2 formulation shows maximum swelling and porosity observed after 12 h. Hence, formulation F2 shows the best formulation among the six formulations containing different binders and super disintegrants.
Keywords: Ciprofl oxacin hydrochloride; direct compression; fl oating tablet; gastroretentive dosage form